Endoscopically assisted selective antegrade cardioplegia in minimally invasive aortic valve replacement for patients with aortic insufficiencyCentral MessagePerspective - Joji Ito, MD; Hiroshi Nakanaga, MD; Hiromi Fujii, MD; Minoru Tabata, MD, PhD, MPH (JTCVS Techniques)
Objective: In minimally invasive aortic valve replacement via a right minithoracotomy for patients with significant aortic insufficiency, optimal cardioplegia delivery procedures remain controversial. This study aimed to describe and evaluate endoscopically assisted selective cardioplegia delivery in minimally invasive aortic valve replacement for aortic insufficiency. Methods: Between September 2015 and February 2022, 104 patients (mean age, 66.0 ± 14.3 years) with moderate or greater aortic insufficiency underwent endoscopically assisted minimally invasive aortic valve replacement at our institutions. For myocardial protection, potassium chloride and landiolol were systemically administered before aortic crossclamping, and cold crystalloid cardioplegia was delivered selectively to the coronary arteries using step-by-step endoscopic procedures. The early clinical outcomes were also evaluated. Results: Eighty-four patients (80.7%) had severe aortic insufficiency, and 13 patients (12.5%) had aortic stenosis and moderate or greater aortic insufficiency. A regular prosthesis was used in 97 cases (93.3%), and a sutureless prosthesis was used in 7 cases (6.7%). The mean operative, cardiopulmonary bypass, and aortic crossclamping times were 169.3 ± 36.5, 102.4 ± 25.4, and 72.5 ± 21.8 minutes, respectively. No patients underwent a conversion to full sternotomy or required mechanical circulatory support during or after surgery. No operative deaths or perioperative myocardial infarctions occurred. The median intensive care unit and hospital stays were 1 and 5 days, respectively. Conclusions: Endoscopically assisted selective antegrade cardioplegia delivery is safe and feasible for treating minimally invasive aortic valve replacement in patients with significant aortic insufficiency.